Evaluation the Concept of Revitalization Pedestrian Path on Raden Saleh Raya Street, Central Jakarta - Ulinata (Talenta Publisher, 2022)
DKI Jakarta Provincial Government is increasing the activation of pedestrian paths with the aim of making the DKI Jakarta region a pedestrian-friendly city so as to reduce the use of private vehicles that use fuel oil that can cause congestion, air pollution that has the potential to damage the environment. DKI Jakarta Provincial Government has also revived the development of urban equipment such as infrastructure and pedestrian sidewalks to encourage citizens to explore the city on foot. Pedestrian paths can now be sidewalks, walkways, squares, and malls. This study aims to evaluate the concept of Revitalization pedestrian path on Raden Saleh Raya Street and whether they meet the design criteria of pedestrian paths and whether there is an increase in the number of residents walking in the area. This study uses quantitative methods. The results show that pedestrian path on Raden Saleh Raya Street are used by pedestrians but some parts of the pedestrian path are used for selling activities, parking motorcycles so that the pedestrian lane has not provided complete comfort so that an improvement strategy is needed to improve pedestrian comfort so that the number of pedestrians using pedestrian path on Jalan Raden Saleh, Central Jakarta, has increased.